2013
DOI: 10.3109/01480545.2013.776581
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and antioxidant enzyme activity induced by hexavalent chromium inCyprinus carpioafterin vivoexposure

Abstract: Fish, being an important native of the aquatic ecosystem, are exposed to multipollution states and are therefore considered as model organisms for ecotoxicological studies of aquatic pollutants, including metal toxicity. We investigated oxidative stress (OS) in liver, kidney and gill tissues through antioxidant enzyme activities and genotoxicity induced in whole blood and gill tissues through comet assay and micronucleus (MN) test in Cyprinus carpio after 96-hour in vivo static exposure to potassium dichromate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…All fish blood cells are nucleated which also represents an important practical advantage (comparing to mammals) for the assessment of genomic integrity. Nevertheless, other somatic tissues like liver, kidney and gills have been also frequently addressed (Guilherme et al, 2012b ; Kumar et al, 2013 ; Velma and Tchounwou, 2013 ), as well as germ cells (Pérez-Cerezales et al, 2010 ). It is recognized that DNA strand breakage can be tissue- and cell-type-specific (Pandey et al, 2006 ).…”
Section: A Methodological Overviewmentioning
confidence: 99%
“…All fish blood cells are nucleated which also represents an important practical advantage (comparing to mammals) for the assessment of genomic integrity. Nevertheless, other somatic tissues like liver, kidney and gills have been also frequently addressed (Guilherme et al, 2012b ; Kumar et al, 2013 ; Velma and Tchounwou, 2013 ), as well as germ cells (Pérez-Cerezales et al, 2010 ). It is recognized that DNA strand breakage can be tissue- and cell-type-specific (Pandey et al, 2006 ).…”
Section: A Methodological Overviewmentioning
confidence: 99%
“…In fish, Cr(VI) has the ability to enter into the cells and react with intracellular components, liberating unstable radicals which can induce oxidative stress, among other toxic effects (Ahmad et al, 2006). In previous studies with other fish species, Cr(VI) was found to induce oxidative stress after acute exposure (Dogan et al, 2014;Kumar et al, 2013;Pacheco et al, 2013). The role of GST enzymes on the anti-oxidant response of fish to chromium-induced oxidative stress is not yet completely understood.…”
Section: General Conditions and Parameters Of Fish In The Control Groupsmentioning
confidence: 98%
“…The LC 50 s determined in the present study (Table 2) compare with corresponding values found in the literature for other fish species. For example, potassium dichromate 96 h-LC 50 s of 35.7 mg/l and 375.8 mg/l were calculated for the freshwater stinging catfish Heteropneustes fossilis (Ahmed et al, 2013), and the common carp Cyprinus carpio (Kumar et al, 2013), respectively, whereas the 96 h-LC50 of Cr(VI) to the zebrafish (Danio rerio) was 39.4 mg/l (Domingues et al, 2010). The effects of Cr(VI) on the predatory performance and selected subindividual biomarkers of early P. microps juveniles are shown in Table 3.…”
Section: General Conditions and Parameters Of Fish In The Control Groupsmentioning
confidence: 99%
“…There are some reports investigating the genotoxicity of K 2 Cr 2 O 7 . [ 24 25 26 ] In a study which is performed in Cyprinus carpio , it has been noted that genotoxicity induced by K 2 Cr 2 O 7 indicated a concentration-dependent increase in DNA damage. [ 24 ] Kaya et al .…”
Section: Discussionmentioning
confidence: 99%